Comparative Study of CaSO4 and Papain Enzyme as Coagulants in The Tofu Production - Windy Rizkaprilisa; Setiadi Setiadi (Indonesian Association of Food Technologists, 2018)
Tofu is a high protein food which is widely consumed in Indonesia. In this study, we used the variety of coagulant which is CaSO4 and papain enzymes. The extraction of soybean protein was conducted using selected ratio (1:2), then coagulated using two different coagulant which are CaSO4 (1 and 2 gram) and papain enzyme (3 and 6 gram). The highest yield of tofu used CaSO4 2 gram with 66% yield and papain enzyme 6 gram with 65% yield. This indicates that more of coagulant are used so more yield of tofu. Based on the proximate test, especially proteins showed the making of tofu with papain enzyme (9.29%) gave higher protein content than CaSO4 (6.50%) as coagulant.Keywords: Tofu, soybean, CaSO4, papain enzyme